(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In spite of the fact that management is accountable for designing and implementing firmstrategies, the ultimate responsibility for determining whether or not such strategies are successful lieswith the employees who put those plans into action. For this reason, it is essential for management tohave a knowledge of the factors that inspire workers to carry out their responsibilities and reach orsurpass the expectations of management. It would be foolish to minimise the value produced by thecompany’s personnel in light of PT XYZ’s outstanding performance in the face of strong competition inthe industry. PT XYZ may be able to better manage its employees if it takes into consideration theincentives it gives to its personnel and identifies which of those incentives have the most influence onthe level of motivation exhibited by its workforce.